Diagnostic performance of positron emission tomography in the staging of pseudomyxoma peritonei. Issue 7 (July 2022) - Flood, Michael P.; Kong, Joseph C.; Pham, Toan; Waters, Peadar S.; Soucisse, Mikael; Ramsay, Robert; Wong, Hui-Li; Mitchell, Catherine; Michael, Michael; McCormick, Jacob J.; Warrier, Satish K.; Akhurst, Tim; et al.
Abstract: Background: Pseudomyxoma peritonei (PMP) is a rare clinical entity, commonly derived from a mucin-producing tumour of the appendix. International consensus is unclear on the role of positron emission tomography (PET) in preoperative staging. This study aimed to assess the ability of preoperative PET in predicting the histological grade of PMP. Methods: All patients scheduled for cytoreductive surgery (CRS) +/− hyperthermic intraperitoneal chemotherapy (HIPEC) for PMP who underwent preoperative PET at a single centre between June 2007 and June 2020 were included. A nuclear medicine physician, blinded to patient outcomes, retrospectively reviewed imaging studies to assess for maximum tumour standardised uptake value (SUV) to mean liver SUV ratio (SUVTLR ) and maximum porta hepatis SUV to mean liver SUV ratio (SUVPLR ). Results: Between April 2007 and December 2020, a total of 204 patients underwent surgical intervention for PMP. Of these, 124 (60.8%) met the inclusion criteria. Median peritoneal carcinomatosis index for the entire cohort was 9 and complete cytoreduction (CC0/1) was achieved in 109 (88%) patients. Patients with high-grade PMP were more likely to have diffuse peritoneal disease (p < 0.001) and higher SUVTLR (p<0.001). The area under the ROC curve (AUC) of SUVTLR in predicting high-grade pathology was 71% (p = 0.003). Patients with a SUVTLR ≤ 0.78 had improved disease-free survival (p = 0.042). Conclusion: Preoperative PET showed positive correlation with high-grade PMP and acceptable sensitivity and specificity as a diagnostic tool. PET should be considered a useful adjunct to standard imaging for predicting histological grade in the staging of patients with PMP.